Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1073/pnas.2014723118
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of aneuploidy in human fibroblasts with trisomy 21

Abstract: An extra copy of chromosome 21 causes Down syndrome, the most common genetic disease in humans. The mechanisms contributing to aneuploidy-related pathologies in this syndrome, independent of the identity of the triplicated genes, are not well defined. To characterize aneuploidy-driven phenotypes in trisomy 21 cells, we performed global transcriptome, proteome, and phenotypic analyses of primary human fibroblasts from individuals with Patau (trisomy 13), Edwards (trisomy 18), or Down syndromes. On average, mRNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 55 publications
10
52
0
Order By: Relevance
“…We also found that aneuploidy states affect cell fate commitment and determination, and influence the development of multiple organs and systems (Figures 2D and 3), which is consistent with the fact that aneuploidy variation usually severely affects the growth and development of organisms [37,38]. Protein stability in aneuploidy cells is also affected, possibly because aneuploidy interferes with protein synthesis and alters sensitivity to protein folding, leading to protein degradation [57,69]. We found that aberrantly expressed genes in Drosophila aneuploidy enriched the function of protein ubiquitination (Figures 2D and 3), revealing that aneuploidy may affect protein degradation by regulating the ubiquitination process.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also found that aneuploidy states affect cell fate commitment and determination, and influence the development of multiple organs and systems (Figures 2D and 3), which is consistent with the fact that aneuploidy variation usually severely affects the growth and development of organisms [37,38]. Protein stability in aneuploidy cells is also affected, possibly because aneuploidy interferes with protein synthesis and alters sensitivity to protein folding, leading to protein degradation [57,69]. We found that aberrantly expressed genes in Drosophila aneuploidy enriched the function of protein ubiquitination (Figures 2D and 3), revealing that aneuploidy may affect protein degradation by regulating the ubiquitination process.…”
Section: Discussionsupporting
confidence: 84%
“…In various studies, common characteristics of aneuploidy driven by genomic imbalance have been identified, such as altered metabolism, lower viability, genomic instability, and altered proteostasis [57,69,70]. In this study, we found that a number of metabolic processes in Drosophila are affected by aneuploidy states, such as organic acid and carbohydrate metabolic process.…”
Section: Discussionmentioning
confidence: 57%
“…Given that chromosome 10 harbors the FGF2R gene, presumably higher levels of this receptor, due to the presence of an extra chromosome 10, may lead to overgrowth of a proliferative clone. Although it is still unclear how aneuploidies may control the expression and transcriptional activities of the genes encompassed within the extra chromosome, Sunyoung Hwang and coworkers recently demonstrated that their mRNA levels increase proportionally with gene copy numbers and that mechanisms required to compensate for the gene expression of an extra copy of a human autosome do not seem to be engaged [30]. SCI13D expressed higher mRNA levels of FGFR2 than the MRC5 lung control cell line; however, further investigations would be of help to better establish a potential link between the presence of an extra chromosome 10 and its putative selective advantage for cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…However, through perturbation of regulatory networks, these changes might also affect transcripts and proteins encoded by genomic regions unaffected by aneuploidy. These were previously defined as 'trans-effects' and have been observed on the transcriptional level in diverse species, including humans, yeast, maize, and Arabidopsis [47][48][49][50] . Here we investigated the extend of trans-effects in Leishmania by comparing and characterizing the fractions of differential transcripts and proteins coming from aneuploid chromosomes, i.e.…”
Section: The Impact Of Aneuploid Chromosomes On the Gene Products Of Their Euploid Counterpartsmentioning
confidence: 99%